Tra civiltà cavalleresca e imprenditorialità rurale: appunti sui castelli subalpininell’autunno del Medioevo - Longhi, Andrea (Opus Incertum, 2016)
The continuous transformation of the structures and functions of castles during the Late Middle Ages is demonstrated throughan interpretation of architecture as the material and stratified result of cultural, political and economic dynamics. This paperidentifies certain institutional and social processes that had an influence on the transformation -in terms both material andof meaning- of rural castles, examined in the period between the consolidation of regional principalities in the fourteenthcentury and the formation of modern states in the second half of the sixteenth century. Certain study cases, which have emergedin recent literature related to the areas belonging to the House of Savoy as well as to Saluzzo, are presented for illustrativepurposes, and may be considered as pilot cases concerning wider and shared dynamics regarding the relationship betweenfortification, residentiality and rural life.